A comparison of cervical cancer screening methods: pap smear, liquid based cytology and VIA VILI - Jeyakumar, Abinaya Maathuri; Mohanapu, Swarnalatha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: There are multiple screening methods available for screening cervical cancer with their advantages and disadvantages, researches that compare the sensitivity, specificity, positive and negative predictive values of these tests in a low-cost setting specific to a geographical area is lacking and has to be enhanced. The objective of this study was to determine and compare the agreement, sensitivity, specificity and predictive values of conventional Pap smear cytology, liquid-based cytology and VIA/VILI with cervix biopsy. Methods: This cross sectional study was conducted on women of >35 years of age. Pap smear specimen was collected followed by Liquid Base Cytology (LBC) using cytobrush specimen after which visual inspection with 5% acetic acid (VIA) and visual inspection with Lugol’s Iodine (VILI) procedure was carried out and followed by cervix biopsy. All methods were analyzed for accuracy. Results: Sensitivity was lowest for PAP smear (39.1%, 95% CI 19.18% to 59.1%), followed by VIA VILI (95.7%, 95% CI 87.32% to 100%), and highest for LBC (100.0%). The negative predictive value was lowest for PAP smear (87.4%, 95% CI 81.21% to 93.6%), followed by VIA VILI (99.0%, 95% CI 96.99% to 100.0%) and highest for LBC (100%). The overall diagnostic accuracy was lowest for PAP smear (88.3%) followed by VIA/VILLI (99.2%) and highest for LBC (100%). Conclusions: Treatment decisions based on findings of the PAP smear have to be taken with caution, considering the lower sensitivity. Wherever resources are available more accurate screening methods like liquid-based cytology must be used.